PENDEKATAN METODE TRIGONOMETRI PADA APLIKASI PEMANTAUAN PROGRES PEMBANGUNAN JALAN BERBASIS ANDROID - Dixy Abdul Rochman S; Lisa Kristiana; Marisa Premitasari (Universitas Widyatama, 2020)
The construction industry such as road construction deals with many problems and uncertainty in the implementation process. In addition, time, cost and quality of work issues are also the focus of project implementation in the field of research services, It starts with the data planning and location coordinates which are aggregated from the project's site by the officer. Those data planning and location coordinates are pin pointed and stored in databases. each point consists of Longitude, Latitude, Road type, and road width. Using the Android application for monitoring, the officer conducts the supervision as required for the determined point in order to update the road construction status, the trigonometric process will directly display the right and left lines for the direction of the photo capturing. however, a long road capturing, the system will take approximately 30 seconds so that GPS can read coordinates correctly